2023
DOI: 10.7759/cureus.42464
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Allergic Bronchopulmonary Aspergillosis With Failure of Benralizumab and Response to Dupilumab

Abstract: We report a case of a 68-year-old woman who was being treated for bronchial asthma and developed allergic bronchopulmonary aspergillosis (ABPA) that was unresponsive to benralizumab therapy but went into remission with dupilumab therapy. The patient presented with an exacerbation of dry cough and was diagnosed with ABPA based on new diagnostic criteria. Despite the attempted therapeutic intervention, the patient declined to use systemic corticosteroids due to concerns about potential side effects. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Anti‐IL‐5/IL‐5 receptor antibodies are highly effective in patients with ABPA, especially for improving mucus plugging 25 . Previous case reports suggested that dupilumab is effective when switching from other biologics to this drug 26–30 . Similar to the present case, the therapeutic efficacy of dupilumab in patients with NTM‐PD 31 and the discontinuation of oral steroids during the use of dupilumab 32 were also observed in patients with ABPA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Anti‐IL‐5/IL‐5 receptor antibodies are highly effective in patients with ABPA, especially for improving mucus plugging 25 . Previous case reports suggested that dupilumab is effective when switching from other biologics to this drug 26–30 . Similar to the present case, the therapeutic efficacy of dupilumab in patients with NTM‐PD 31 and the discontinuation of oral steroids during the use of dupilumab 32 were also observed in patients with ABPA.…”
Section: Discussionsupporting
confidence: 87%
“… 25 Previous case reports suggested that dupilumab is effective when switching from other biologics to this drug. 26 , 27 , 28 , 29 , 30 Similar to the present case, the therapeutic efficacy of dupilumab in patients with NTM‐PD 31 and the discontinuation of oral steroids during the use of dupilumab 32 were also observed in patients with ABPA. Of note, dupilumab treatment was associated with a reduced incidence of respiratory infections in patients with moderate‐to‐severe asthma or severe CRSwNP.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…NEW TREATMENT METHOD FOR ABPM reported cases of ABPM that responded to dupilumab, the mucus plugs were relatively small or located peripherally. 1,2 When a relatively large mucus plug located centrally results in atelectasis, as in the present case, treatment with dupilumab alone may take longer to improve clinical symptoms. The second reason was the need to focus on the mechanisms of mucus plug formation in ABPM and the fact that ABPM is caused by type I and type III hypersensitivity reactions to filamentous fungi.…”
Section: Discussionmentioning
confidence: 59%
“…Several case reports in recent years have described successful treatment of allergic bronchopulmonary mycosis (ABPM) with dupilumab, 1 , 2 but none have reported multidisciplinary treatment with dupilumab and a cryoprobe after visualizing mucus plugs obstructing the entire bronchus using 3‐dimensional (3D) computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%